Associate Professor Ts. Dr. Roshahliza produce system used solar irrigation drip through IoT method - Safriza, Baharuddin (UMPSA, 2023)
PEKAN, 17 October 2023 - PaTrIoT, an abbreviation for Parit Tray IoT, is a solar irrigation system that utilizes drip irrigation to water small planting areas for oil palm seedlings, utilizing Internet of Things (IoT) technology.